Cystic Dilation of Extrahepatic Bile Ducts in Adulthood: Diagnosis, Surgical Treatment and Long. Term Results. Issue 6 (1998) - Belli, G.; Rotondano, G.; D'Agostino, A.; Iannelli, A.; Marano, I.; Santangelo, M. L.
Abstract : To evaluate the long-term results of surgery for choledohal cyst in adulthood, a series of 13 patients over the age of 16 operated on for choledochal cyst during a period of six years and followed-up for a minimum of 3 years was analyzed. Patients with type I and IVa cysts underwent extrahepatic cyst resection and Roux-en-Y hepatico-jejunostomy. Choledochoceles (type III) were managed endoscopically. No operative mortality or morbidity occurred. Type I and III cysts showed almost ideal follow-up with no sign of stricture on HIDA scan. One type IVa cyst patients developed recurrent cholangitis due to anastomotic stricture, managed percutaneously. Whenever possible, complete cyst resection and Roux-en-Y reconstruction is the treatment of choice for all extrahepatic biliary cysts. Intra- and extrahepatic dilatations are adequately treated by extrahepatic resection and careful endoscopic or radiologic surveillance. Small choledochoceles can be safely managed by endoscopic sphincterotomy.